Clinical follow‐up of 411 patients with relapsing and progressive multiple sclerosis 10 years after discontinuing mitoxantrone treatment: a real‐life cohort study. (3rd August 2018) - Chartier, N.; Epstein, J.; Soudant, M.; Dahan, C.; Michaud, M.; Pittion‐Vouyovitch, S.; Guillemin, F.; Debouverie, M.; Mathey, G.
Abstract : Background and purpose: Mitoxantrone (MITOX) has been used to treat patients with aggressive multiple sclerosis (MS) for decades. We aimed to describe the effectiveness and adverse events over 10 years post‐MITOX in patients with relapsing and progressive MS from an exhaustive real‐life database. Methods: Data from patients who received MITOX before 1 January 2006 were collected from the MS Lorraine registry. Expanded Disability Status Scale (EDSS) scores and annual relapse rates (ARRs) year by year during follow‐up and the year prior to MITOX were compared. Time to the first relapse and a 1‐point increase in EDSS score were used in Cox multivariate models to find associations with potential predictive factors. Results: A total of 411 patients were included. The ARR for the 155 relapsing patients had decreased from 2.0 (SD 1.20) the year before treatment to 0.3 (SD 0.31) by year 10 ( P < 0.0001). The EDSS score increased from 2.8 (SD 1.44) to 4.8 (SD 1.90) by year 10 ( P < 0.0001). A high ARR at MITOX initiation was associated with a longer time to a 1‐point increase in EDSS score (hazard ratio, 0.81; 95% confidence interval, 0.67–0.99; P = 0.04). The EDSS score in 256 progressive patients increased from 5.0 (SD 1.33) to 6.5 (SD 1.26) by year 10 ( P < 0.0001). We identified four cases of acute myeloid leukemias. Conclusions: Patients with the most active forms of MS are the most likely to benefit from MITOX in the long term. Abstract : Clickhere to view the accompanying paper in this volume.